Balancing sensory inputs: somatosensory reweighting from proprioception to tactile sensation in maintaining postural stability among older adults with sensory deficits - Liu, Ziyin; Wang, Qi; Sun, Wei; Song, Qipeng (Frontiers in Public Health, 2023)
Background Sensory deficits increase the risk of falls among older adults. The purpose of this study was to investigate the correlations of lower extremity muscle strength, proprioception, and tactile sensation to postural stability among older adults with and without sensory deficits, to understand the contribution of each factor to postural stability, and to explore sensory reweighting among the two populations. Methods A total of 103 participants were recruited and divided into two older adult groups with (female = 24, male = 26, age = 69.1 ± 3.15 years, height = 162.72 ± 6.94 cm, body mass = 64.05 ± 9.82 kg) and without sensory deficits (female = 26, male = 27, age = 70.02 ± 4.9 years, height = 163.76 ± 7.60 cm, body mass = 65.83 ± 10.31 kg), based on whether a 5.07 Semmes–Weinstein monofilament could be detected at foot soles. Their Berg Balance Scale (BBS), lower extremity muscle strength, proprioception, and tactile sensation were tested and compared between the two groups. Pearson's or Spearman's correlations were used to explore the relationships between the BBS and each variable. Factor analysis and multivariate linear regression were used to verify the degrees of correlation between the generated factors and the postural stability. Results Low BBS (p = 0.003, η2 = 0.088) scores and higher proprioception thresholds (knee flexion: p = 0.015, η2 = 0.059; knee extension: p = 0.011, η2 = 0.065; ankle plantarflexion: p = 0.006, η2 = 0.075; ankle dorsiflexion: p = 0.001, η2 = 0.106) were detected among older adults with sensory deficits compared with those without sensory deficits. Lower extremity muscle strength (ankle plantarflexion: r = 0.342, p = 0.002; hip abduction: r = 0.303, p = 0.041) and proprioception (knee flexion: r = −0.419, p = 0.004; knee extension: r = −0.292, p = 0.049; ankle plantarflexion: r = −0.450, p = 0.002; ankle dorsiflexion: r = −0.441, p = 0.002) were correlated with BBS among older adults without sensory deficits, while lower extremity muscle strength (ankle plantarflexion: r = 0.501, p<0.001; hip abduction: r = 0.302, p = 0.041) and tactile sensation (great toe: r = −0.388, p = 0.008; 5th metatarsal: r = −0.301, p = 0.042) were correlated with BBS among older adults with sensory deficits. Conclusion Older adults with sensory deficits have poorer proprioception and postural stability. Somatosensory reweighting occurs from proprioception to tactile sensation among older adults with sensory deficits in maintaining postural stability.